The Meaning of Profit for Krempyeng Market Gresik’s Merchants through the Cultural Perspective - Syafitri, Isnaini Nur Azizah (Interdisciplinary Social Studies, 2022)
In the economic process, culture is needed. Accounting principles actually vary depending on the cultural variations owned by a country. Culture affects economic processes as well as the main determinants of economic events. This study aims to analyze the meaning of profit from a cultural perspective at Krempyeng Gresik Market traders. This study uses a qualitative approach, the informants in the study amounted to 5 (five) informants, namely the Gresik Krempeng Market traders. The selection of informants in this study used the Snowball sampling technique. Data collection techniques using observation and interviews. The data analysis used in this research is using data reduction, data presentation, and verification/conclusion. Based on the results of research and discussion on the meaning of profit in a cultural perspective at Krempyeng Gresik Market traders, the researchers concluded that the value of service quality and the value of Islamic business ethics can have an impact on social values through the mediation of religious values.